Manufaktur Baut-Mur M8 Panjang 30 mm Bahan SS304, Kapasitas 50 Biji/Jam - Galih Anugrah Putra Septiawan; Syamsul Hadi; Mukhamad Riyan Catur Abimanyu; Muhammad Rafi’yoga Prasojo; Hikmawan Ridho Firdaus (International Forum of Researchers and Lecturers, 2026)
The manufacturing method includes: design of 30 mm long M8 steel bolts and nuts; selection of 8 mm diameter SS304 material in the form of rolls with a diameter of approximately 60 cm; straightening and reducing the diameter from 8 mm to 7.9 mm; cold heading into a round head; cold heading into a hexagonal head; cutting 30 mm long bolts; threading with a threading machine; chamfering the bolt ends; cold heading into a 10 mm round head; cold heading into a 10 mm hexagonal head; cutting 10 mm long M8 nut candidates; threading M8 inner nuts with a tapping machine, chamfering 2 nut thread faces; and quality inspection by thread and dimension samples. The manufacturing results are 30 mm long M8 steel bolts and nuts made of SS304 with a total manufacturing cost of IDR 4,500/piece, and a process duration of 1.2 minutes/piece which means that the construction with these bolts and nuts does not have the potential to be a source of rust.